Can 900 MHz and 2100 MHz radiofrequency radiation exposure induce endoplasmic reticulum stress and apoptosis in rat thymus? - Kaya, Ergi; Kırımlıoğlu, Esma; Er, Hakan; Okan, Aslı; Özen, Şükrü; Demir, Necdet (The European Research Journal, 2023)
Objectives: Electrical appliances are source of radiofrequency radiation (RFR). The effects of RFR on the organism are not fully understood. Endoplasmic reticulum (ER) stress is appeared by the accumulation of misfolded proteins in ER lumen. The aim of this study was to investigate the effects of 900 and 2100 MHz RFR exposure on the ER stress pathway in rat thymus. Methods: Rats were divided into six groups: 1 week (w) and 10 w Sham rats were kept in plexiglass tubes for 2 hours/day without RFR, experiment groups were created as 1-w (acute) and 10 w (chronic) rats which exposed to 900 and 2100 MHz RFR for 2 h/day. There were 20 male Wistar rats in each group. Immunohistochemistry stainings were performed GRP78, CHOP, Cleaved (Clv.) Caspase 3 and Caspase 12. Results: Expressions of GRP78 and Clv. Caspase3 in RFR groups is significantly higher than sham groups (p < 0.001). In 900 MHZ-1 w rats, high levels of GRP78 expressions were at the cytoplasm of epithelial reticular cells. In other groups, GRP78 expressions were seen also at thymocytes. Expressions of CHOP in RFR rats were higher than sham rats (2100 MHz /Sham for 10 w; p < 0.001, 900 MHz /Sham for 10 w; p = 0.004, 900 MHz /Sham for 1 w; p = 0.003). Localization of CHOP expressions was at the nucleus membrane and cytoplasm. The expression of Caspase 12 in RFR rats was higher than sham rats (900 MHz /Sham for 1 w; p = 0.006, other groups; p < 0.001). Conclusions: This study demonstrates RFR exposure could increase levels of ER stress pathway proteins and could cause apoptosis.